Police Preventive Strategy: The Effectiveness of Situational Crime Prevention in Controlling Prostitution Venues in Region X South Jakarta - Nurhadiyanto, Lucky; Anorawi, Rafi; Rozak, Abdur (PT FORMOSA CENDEKIA GLOBAL, 2024)
Prostitution is a complex and intractable social problem in many countries, including Indonesia. The Blok M area, located in South Jakarta, has long been known as the center of prostitution activities. The method used in this research is a qualitative method using interview techniques, observation and literature study. The result of this research is that the police encourage active participation of the community in reporting prostitution activities and providing useful information for investigation. In addition, the police try to raise public awareness about the negative impact of prostitution and provide rehabilitation and social assistance to victims of prostitution who want to get out of the cycle of violence and exploitation. Despite the police's efforts, the problem of prostitution in the Blok M area cannot be fully addressed overnight. Prostitution involves a wider range of social, economic and cultural factors. Therefore, cooperation between the police, government, and the community must be continuously improved to achieve sustainable results in eradicating prostitution and protecting the community from its negative impacts. By analyzing the police's efforts in controlling prostitution venues in the Blok M area, this research is expected to provide a better understanding of the challenges and strategies applied in combating the problem of prostitution and provide input for more effective policies and measures in addressing this complex social problem.